Reading the Sensual in James Baldwin’s Giovanni’s Room - Ronnel Keith Berry; Michael Thomas (Transatlantica)
In The Fire Next Time, African American writer James Baldwin describes the sensual as, “respect[ing] and rejoice[ing] in the force of life, of life itself, and to be present in all that one does, from the effort of loving to the breaking of bread” (1998c 311). Baldwinian sensuality is divorced from its hedonistic interpretation, instead expressing a form of knowledge and a practice of living in openness to each other and the complexity of our humanity. In his essays and novels, Baldwin works at the intersection of his readers’ “sense of reality,” or lived experience of the world, and “system of reality,” the sociological structure in which they are positioned. In this article, we read Giovanni’s Room (1956) as a site for identifying Baldwin’s techniques for evoking the sensual and experimenting with its effects on individuals and the postwar system(s) of reality. These techniques connect Baldwin’s literary persona and its transformations with the form and content of his essays, providing a framework for analyzing the tension between heteronormative love and queer desire experienced by David in the novel. Using this analysis, we articulate a Baldwinian theory of the sensual as a site for interventions against the racism and homophobia generated by our 21st-century system of reality and as a source of techniques for altering our sense of reality to make systemic transformations possible.